Analisis Social Return On Investment (SROI) Pada Program Entrepreneurship Workshop - Arman Arman; Tri Siwi Agustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Social Return on Investment (SROI) is a technique to measure the impact/benefit of a project or program. This study aims to analyze the impact of social investment from the implementation of the program, Entrepreneurship Workshop